A methodological framework to support energy decision-makers in investment planning for energy efficiency programs in the residential sector - Lima, João André Viseu Simões (2020)
Dissertação de Mestrado Integrado em Engenharia Electrotécnica e de Computadores apresentada à Faculdade de Ciências e Tecnologia